2008
DOI: 10.3852/08-015
|View full text |Cite
|
Sign up to set email alerts
|

GAC1, a gene encoding a putative GTPase-activating protein, regulates bikaverin biosynthesis inFusarium verticillioides

Abstract: Fusarium verticillioides (teleomorph Gibberella moniliformis) is an ascomycete known to produce a variety of secondary metabolites, including fumonisins, fusaric acid and bikaverin. These metabolites are synthesized when the fungus is under stress, notably nutrient limitations. To date we have limited understanding of the complex regulatory process associated with fungal secondary metabolism. In this study we generated a collection of F. verticillioides mutants by using REMI (restriction enzyme mediated integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Here were presented proofs, that not only GAC1, but Fpacy1, a downstream element of the cAMP-PKA signaling pathway also represses the biosynthesis of this secondary metabolite. On the other hand, mutations of neither the GAC1 gene of F. verticillioides [43], nor Fpacy1 of F. proliferatum (present study) affected FB1 biosynthesis. The stress stimuli needed to trigger fumonisin biosynthesis is mediated via another signaling pathway, the HOG-type MAPK route, as has recently been demonstrated [44].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Here were presented proofs, that not only GAC1, but Fpacy1, a downstream element of the cAMP-PKA signaling pathway also represses the biosynthesis of this secondary metabolite. On the other hand, mutations of neither the GAC1 gene of F. verticillioides [43], nor Fpacy1 of F. proliferatum (present study) affected FB1 biosynthesis. The stress stimuli needed to trigger fumonisin biosynthesis is mediated via another signaling pathway, the HOG-type MAPK route, as has recently been demonstrated [44].…”
mentioning
confidence: 87%
“…Bikaverin is a polyketide secondary metabolite with antiprotozoal and antifungal activity [18,41] and its production is triggered by stress factors, like nitrogen depletion [42]. Recent studies demonstrated that GAC1, a putative GTPase activator protein gene of Fusarium verticillioides (a close relative of F. proliferatum) negatively regulates bikaverin production [43]. The authors postulated that GAC1 is involved in trafficking proteins through the nucleus membrane and they necessitated further research to understand the signaling pathway that directly regulates bikaverin synthesis.…”
mentioning
confidence: 99%
“…20 Fusaric acid (2) has been described to be produced in Fusarium verticillioides under stress conditions, notably, nutrient limitations. 21 The metabolite has been described as an inhibitor of metal-containing oxidative enzymes, such as dopamine-b-hydroxylases, phenylethanolamine methyltransferase and catechol oxidase. 22 Nonpathogenic Fusarium oxysporum species have been described as an potential biocontrol agents, producing only 2 and dehydrofusaric acid, but no other toxins.…”
Section: Discussionmentioning
confidence: 99%
“…OTA biosynthesis may be influenced by eco physiological intrinsic factors, such as temperature, nitrogen shortage and pH conditions which also influence germination, growth and sporulation (Palacios-Cabrera et al, 2005;Garcia-Cela et al, 2014;Passamani et al, 2014). Under stress conditions, the signaling pathways certainly induce the production of mycotoxins (Choi et al, 2008;Kohut et al, 2009).Therefore, understanding the effects of these factors can help reduce mycotoxins, both in the field and during storage. Furthermore, interactions between mycotoxigenic species and other spoilage fungi can significantly influence ochratoxin A production (Lee and Magan, 2000).Several authors have studied the ability of A. ochraceus and A. carbonarius to produce OTA in coffee, maize and synthetic grape and barley medium under different environmental conditions (Pardo et al, 2005;Lee and Magan, 2000;Marín et al, 2006;Pardo et al, 2004;Garcia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%